High-Temperature Tensile Properties and Serrated Flow Behavior of FeCrAl Alloy for Accident-Tolerant Fuel Cladding - Mengyu Chai; Zelin Han; Hao Su; Hao Li; Pan Liu; Yan Song (Applied Sciences)
The development of FeCrAl alloys has commenced for use as nuclear fuel cladding material, intended to serve as an enhanced accident-tolerant alternative to Zr-based alloys. In this study, the Fe-13Cr-4Al alloy, specifically designed for advanced accident-tolerant fuel (ATF) cladding, was carefully prepared through vacuum induction melting and hot-working processes. Mechanical properties and serrated flow behavior of this alloy were investigated through tensile tests at temperatures ranging from 200 to 800 °C. Intriguingly, serrations emerged within a specific temperature range, accompanied by unique mechanical behavior characteristics indicative of dynamic strain aging (DSA). Additionally, the alloy’s fracture modes showed a transition from a mix of ductile and cleavage fracture features to fully ductile fracture as the temperature increased. This study offers insights into the mechanical properties and serration behaviors of FeCrAl alloys, highlighting their potential for use in nuclear fuel cladding.